Program Mbkm: Sebuah Dilema Bagi Perguruan Tinggi? - Syahril Syahril; Karunia Puji Hastuti, M.Pd; Deasy Arisanty (Universitas Lambung Mangkurat, 2023)
The Merdeka Belajar-Kampus Merdeka (MBKM) program policy issued by the Minister of Education and Culture has been introduced and implemented in 2020 in all public/private universities in Indonesia. Since its inception, the program has been a real challenge for all colleges to carry it out on their respective campuses. Various responses from the academic community have been given to improve the MBKM program. This research approach uses the library research method. In literature, data is obtained through scrutiny of related literature in the form of articles, books, documents, and scrutiny of online literature. Furthermore, the data is analyzed and described according to the theme discussed. The results of the implementation of the MBKM program show that there are several advantages that have a positive impact on the academic community, especially students. But in addition, the MBKM program also has several disadvantages. Therefore, several solutions are needed to overcome these weaknesses. One of them is through careful planning, socialization, and evaluation together from various related elements. So that the objectives of the MBKM program can be achieved properlyKeywords: MBKM, academic community, universities